Uncovering the Enolase Gene (eno) and Its Role in Biofilm Formation in Clinical Isolates of Staphylococcus aureus - Setiabudy, Marta; Widhidewi, Ni Wayan; Wijaya, Putu Austin Widyasari; Santoso, Putu Nia Calista; Suryawan, Kadek (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2024)
Background: Enolase is an enzyme potentially possessed by Staphylococcus aureus (S.aureus) bacteria, which holds essential virulence factors in human infections. The eno gene that encodes enolase is important in attachment to host cells, leading to biofilm formation, evasion of host immune response, and bacterial central metabolism. This biofilm formation might complicate the therapy. Purposes: This study aimed to assess the prevalence of the enolase gene, namely eno, in clinical isolates of S.aureus and its association with biofilm production. Methods: The research was conducted from December 1, 2023, to February 29, 2024, at the Faculty of Medicine and Health Science Research Laboratory, Warmadewa University. This study employed an analytical approach with a cross-sectional design. Result: The collected samples comprised 18 isolates of S.aureus, 66.6% of which produced biofilm. Most of the S.aureus clinical isolates 17 (94.4%) were detected to have the eno gene. Six samples (33.3%) formed weak biofilm followed by strong and moderate, with the same number of 3 isolates each (16.7%). No correlation between the enolase gene and biofilm production in this study suggested phenotypic heterogeneity, environment and time forming biofilm in vivo differences, and various other genes that influence biofilm formation. Conclusion: The high prevalence of the enolase gene in these clinical isolates indicates the potential for more severe infections in patients related to its adherence, which leads to biofilm and resistance problems and metabolic function.